APPLICATION OF VISUAL LEARNING MODELS, AUDITORY, KINESTETIC (VAK) ON THE RESULTS OF LEARNING SCIENCE CLASS V BANGUNREJO STATE ELEMENTARY SCHOOL - Ernita Sary; Zico Fakhrur Rozi; Tio Gusti Satria (Yayasan Citra Dharma Cindekia, 2020)
This study aims to determine the learning outcomes of the fifth grade students of Bangun Rejo State Elementary School after implementing the Visual, Auditory, Kinestetik (VAK) Learning Model in science learning can be completed significantly. This research is a quasiexperimental research without any comparison class. Sampling using Simple Random Sampling technique. Data collection was done by using test techniques. The data collected were analyzed using t-test at a significant level of ? = 0.05. The results of data analysis can betcount = 4.65 ? ttable = 1.71, so it can be concluded that the learning outcomes of Bangun Rejo Elementary School students after the application of the Visual, Auditory, Kinestetik (VAK) learning model are significantly complete.